Implementation of The Management of Amil Zakat Institutions in Indonesia - Maghfiroh, Siti; Ansori, Saiful (Islamic Studies Journal, 2023)
The population of the State of Indonesia in 2023 will reach 277.23 million people with 85% being Muslim (BPS, 2023). With this population, Indonesia has enormous potential, especially in the fundraising of zakat, infaq, and alms and endowments. The process of fundraising zakat, infaq, alms certainly requires an institution that is able to manage it with good management. One such institution is the Amil Zakat Institution (LAZ). One way to maintain a good level of trust is to maintain an internal control system as well as present transparent and accountable financial reports. In carrying out these demands LAZ must refer to a strong financial management system. For this reason, knowledge of financial management is very important for LAZ, especially for amil who carry out the main tasks and functions of finance. The method in this article is to use the library research method with a phenomenological approach. Where almost Islamic banking in Indonesia is faced with the problem of agency theory. Research results show that the National Amil Zakat Agency (BAZNAS) as the highest national institution in the management of zakat has considered the need to improve effectiveness, efficiency, transparency and accountability in all lines of amil entities, so it is important to regulate the mechanism of zakat financial management. This zakat financial management mechanism is contained in the BAZNAS Regulation consist of Budgeting, Receipt of Funds, Storage of Funds, Withdrawal of Funds, Bookkeeping and Archiving, Control